2019
DOI: 10.1007/s00167-019-05397-3
|View full text |Cite
|
Sign up to set email alerts
|

Acute reconstruction results in less sick-leave days and as such fewer indirect costs to the individual and society compared to delayed reconstruction for ACL injuries

Abstract: Purpose To compare the total number of sick-leave days caused by the knee injury from the day of injury and over the first year between acute (within 8 days) and delayed (6-10 weeks) anterior cruciate ligament reconstruction (ACLR) and also assess other clinical outcomes during this period. Methods Seventy patients with an acute ACL injury and Tegner level of 6 or more were randomized to acute (within 8 days) or delayed (after 6-10 weeks) ACLR. Patient-reported outcomes; objective IKDC and manual stability mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…This suggests early surgery, before recurring giving ways have occurred, decreases additional injuries, and increases the likelihood of FR. Finally, it should be mentioned that an acute ACLR has been shown to be more cost-effective than delayed surgery, and time spent on rehabilitation before the surgery is better utilized postoperatively [ 23 , 27 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests early surgery, before recurring giving ways have occurred, decreases additional injuries, and increases the likelihood of FR. Finally, it should be mentioned that an acute ACLR has been shown to be more cost-effective than delayed surgery, and time spent on rehabilitation before the surgery is better utilized postoperatively [ 23 , 27 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also we might be more reserved with an early ACL reconstruction in younger patients, because young and active patients have the highest risk of a new knee injury possibly and the young might be helped more in the long run with adjustment of their activity level. 8 Von Essen et al 13 found that acute reconstruction resulted in less sick-leave days and fewer indirect costs to the individual and society and was cost-effective. But they did not take into account that 50% of patients treated with a rehabilitation programme are doing well with this treatment and were not reconstructed after all.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published on the costs of ACL reconstruction with different grafts and with a decision-tree analysis for competitive athletes, but so far not with the use of real patient-data of a randomised controlled trial. [11][12][13] The aim of this study was to evaluate the cost-utility of early ACL reconstruction (index) versus rehabilitation plus an optional reconstruction after acute ACL rupture (comparator) with the use of data of a randomised controlled trial.…”
Section: Introductionmentioning
confidence: 99%
“…16 Treating these patients nonoperatively also increases the time from injury to return to sports, as their time from injury to surgery increases, and increases the indirect costs by requiring longer sick leave time. 27…”
mentioning
confidence: 99%
“…16 Treating these patients nonoperatively also increases the time from injury to return to sports, as their time from injury to surgery increases, and increases the indirect costs by requiring longer sick leave time. 27 When reviewing these advantages and disadvantages, there does not seem to be one clear strategy for all patients, and treatment may depend on individual patient characteristics. It is important to assess the role of these individual patient characteristics in the success of nonoperative ACL treatment to advise patients to either start nonoperative treatment with optional delayed ACL surgery, and potentially avoid surgery, or perform early ACL surgery and potentially avoid meniscal and chondral injury and have shorter time from injury to surgery.…”
mentioning
confidence: 99%